2005
DOI: 10.1111/j.1472-765x.2005.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A-producing species in grapes and sun-dried grapes and their relation to ecophysiological factors

Abstract: Aims: To explain the dominance of OTA-producing fungal species in sun-dried grapes for special wine production through an ecophysiological approach. Methods and Results: Grapes at different ripening stages, sun-dried grapes and raisins were analysed for fungal presence, and isolates identified. Aspergillus section Nigri incidence in grapes increased with grape maturation. In the ecophysiological study five isolates (Alternaria alternata, Cladosporium herbarum, Penicillium decumbens, Aspergillus carbonarius, A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 24 publications
2
55
1
4
Order By: Relevance
“…Aspergillus carbonarius was the predominant fungal source of OTA in dried vine fruits examined in Spain and Argentina (Abarca et al 2003;Magnoli et al 2004;Valero et al 2005). Other OTA-producing fungi which have been isolated from grapes or dried vine fruit and are probable contributors to its presence in dried vine fruits include A. niger var.…”
Section: Mycotoxins In Dried Vine Fruitmentioning
confidence: 99%
“…Aspergillus carbonarius was the predominant fungal source of OTA in dried vine fruits examined in Spain and Argentina (Abarca et al 2003;Magnoli et al 2004;Valero et al 2005). Other OTA-producing fungi which have been isolated from grapes or dried vine fruit and are probable contributors to its presence in dried vine fruits include A. niger var.…”
Section: Mycotoxins In Dried Vine Fruitmentioning
confidence: 99%
“…The maximum level of OTA allowed in dried vine fruits in Europe is 10 µg/kg (12). Moreover, Aspergillus niger aggregate and Aspergillus carbonarius have been blamed as the OTA producers in grape and grape-derivatives (13)(14)(15). Astoreca et al (16) reported that, throughout the grape drying process, the biodiversity index showed a decreasing trend because the water activity (Aw) of grape was decreasing and the sugar level was increasing.…”
Section: Introductionmentioning
confidence: 98%
“…and Rhizopus spp. These genus are regarded as the main natural contaminants of grapes (Valero et al, 2005). Changes in the total fungal population over the growing season have been observed.…”
Section: Introductionmentioning
confidence: 99%